Analysis of Geotechnical-Assisted 2-D Electrical Resistivity Tomography Monitoring of Slope Instability in Residual Soil of Weathered Granitic Basement - Olabode, Oladunjoye P.; San, Lim H.; Ramli, Muhd H. (Frontiers in Earth Science, 2020)
Prolong heavy rainfall is increasingly inducing slope instabilities on the high-risk hills of weathered granitic basement in Penang. These slope instabilities are spatially controlled with changes in geotechnical properties of the slope soils. A reliable method to include density as part of geotechnical properties to calibrate electrical resistivity tomography (ERT) resistivity distribution in slope instability monitoring is still rare. Hence, we present six ERT data that were acquired with a survey length of 60 m and 1.5 m electrode spacing using Wenner–Schlumberger array from 2019 to 2020. The results were calibrated with the laboratory-determined geotechnical properties: moisture content (MC), particle-size distribution, density, and hydraulic conductivity (HC). The result of the analysis of ERT models classified resistivity distribution into saturated zones of <600 Ωm with a high percentage of >20% silt and clay, weak zones of 600–3,000 Ωm, and basement rocks of >5,000 Ωm. The presence of floaters and boulders of resistivity >4,000 Ωm overlie saturated zones coupled with multiple rainfall events that act as triggering factors for slope instability and failure. Geotechnical results show strong correlation of R ≈ 0.94 between density and resistivity values which are crucial for the calibration of the ERT models because low-resistivity <600 Ωm areas have high MC, 30.1% with low density, 1,176 kg/m3, and HC, 2.02 × 10–5 m/s, whereas high resistivity <3,000 Ωm areas have lower MC, 11.4% with relatively high density 1,458 kg/m3, and HC, 1.34 × 10–2 m/s. Therefore, we conclude that low-resistivity areas are composed of earth materials that are less-dense low-permeable unstable zones of displacement which constitute subsurface drainage paths that are precursors to slope instability.